2002
DOI: 10.1002/jcb.10059.abs
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol suppresses proliferation of cultured human colon and liver cancer cells by inhibiting DNA synthesis and activating apoptosis

Abstract: Magnolol, a hydroxylated biphenyl compound isolated from the Chinese herb Hou p'u of Magnolia officinalis, has been reported to have anti-cancer activity. In the present study, magnolol at very low concentrations of 3-10 microM inhibited DNA synthesis and decreased cell number in cultured human cancer cells (COLO-205 and Hep-G2) in a dose-dependent manner, but not in human untransformed cells such as keratinocytes, fibroblasts, and human umbilical vein endothelial cells (HUVEC). Magnolol was not cytotoxic at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…As previously described [16,17], the cells were seeded on 100 mm‐dishes and grown in RPMI‐1640 supplemented with 10% FCS. After the cells had grown to subconfluence, they were treated with 0.1% DMSO with or without 100 nM TPA (control).…”
Section: Methodsmentioning
confidence: 99%
“…As previously described [16,17], the cells were seeded on 100 mm‐dishes and grown in RPMI‐1640 supplemented with 10% FCS. After the cells had grown to subconfluence, they were treated with 0.1% DMSO with or without 100 nM TPA (control).…”
Section: Methodsmentioning
confidence: 99%
“…Magnolol, a primary active ingredient of the Chinese medicinal herb Magnolia officinalis , displays a variety of pharmacological activities including anti‐oxidant and anti‐inflammatory activities and central nervous system depressant effects . Recent studies have indicated that magnolol induces antiproliferative effects by blocking DNA synthesis and by inducing apoptosis and cell cycle arrest in a wide variety of tumor cells including colon, liver, and ovarian cancer cells . However, the effects and mechanism of magnolol on human GBC cells have never been elucidated.…”
mentioning
confidence: 99%
“…To determine the expression levels of cSrc, p‐cSrc, FAK, paxillin, RhoA, RhoB, RhoC, Rac‐1, cadherin, and G3PDH in HUVECs, the total proteins were extracted and Western blot analyses were performed as previously described [Lin et al, ]. Briefly, HUVECs were cultured in 10 cm Petri dishes.…”
Section: Methodsmentioning
confidence: 99%